Epilepsy syndromes: the 2022 ILAE definition and classification - D. V. Blinov (Эпилепсия и пароксизмальные состояния)
Until recently, no classification of epileptic syndromes officially approved by the International League Against Epilepsy (ILAE) was available. In 2022, owing to many year-persistent efforts made by experts and the public community, the studies providing the definition and classification of epileptic syndromes were published. ILAE has approved the following definition of the epileptic syndrome: “a characteristic cluster of clinical and EEG features, often supported by specific etiological findings (structural, genetic, metabolic, immune, and infectious)”. The classification of epileptic syndromes is proposed according to the age principle: onset in neonates and infants, onset in childhood, onset at a variable age. Separately, the syndromes of idiopathic generalized epilepsy were presented. Clinical data for each epileptic syndrome are presented in a single pattern: epidemiology, clinical context, natural history, type(s) of seizures, electroencephalography, neuroimaging findings, genetic findings, other laboratory findings (when informative), differential diagnosis. The criteria for diagnosis, including mandatory criteria, warning signs and exclusion criteria, are given. This classification should be a starting point for further improvement in the organizing work of practitioners who deal with epilepsy.